Analisis Pengaruh Struktur Kepemilikan Dan Karakteristik Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Anita, Anita (Faculty of Economics, Universitas Internasional Batam, 2018)
This study aims to analyze the effect of ownership structure and firm characteristics on CSR disclosure in companies listed on the Indonesia Stock Exchange. These ownership structure and firm characteristics are managerial ownership, institutional ownership, government ownership, foreign ownership, firm size, profitability, leverage, industry type, age and size of audit firm to CSR disclosure. The sample consists of 330 companies listed on the Indonesia Stock Exchange from 2010-2014 which are taken by purposive sampling method. Data analysis method used in this study is panel data regression. Results indicate that government ownership, foreign ownership, firm size, industry type, firm age and size of audit firm are significantly and positively related to CSR disclosure, while institutional ownership is significantly and negatively related to CSR disclosure. The results also display no significant relationship between managerial ownership, profitability, and leverage and CSR disclosure.